Administrative law - Craig, P. P. (Delhi, 1996)
Almost every aspect of modern life is now touched by admin istrative law, a subject that is of ever-increasing importance both for students and those in practice. The second edition of Administrative Law offers complete and detailed discussion of the law, placing it within its historical, social and political framework. Throughout, administrative policies and judicial decisions are analysed in depth, and possible solutions to difficult controversial questions thus arising are suggested to assist complete understanding of this complex area of law. Many major new decisions are analysed in detail, and com parisons are made with other jurisdiction, particularly that of the United States. Full consideration has been given to recent research in the area, and the implications which flow from the important privatisation programme are discussed. Craig's bold approach to administrative law, so successful in its first edition, will continue to stimulate thought and dis cussion among all those interested in administrative law, whether practitioners, lecturers or students.
Keywords: Administrative law